Strategi Optimalisasi Kesejahteraan Narapidana Disabilitas Di Lembaga Pemasyarakatan - Diosand, Revaldo Putra; Subroto, Mitro (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to identify the welfare conditions of disabled prisoners in correctional institutions, examine optimization strategies that can be applied to improve the welfare of disabled prisoners and the implementation of optimization strategies in improving the welfare of disabled prisoners in correctional institutions. Based on the findings, there are major obstacles to inadequate infrastructure in many correctional institutions that are not designed to accommodate the special needs of disabled prisoners. This study uses a qualitative approach with a case study method. This study will analyze the welfare conditions of disabled prisoners in several correctional institutions in Indonesia, as well as evaluate the implementation of optimization strategies that have been applied. The results of the study show the specific needs of disabled prisoners, recommendations for effective strategies to improve welfare, assessment of the implementation and impact of the strategies implemented